Biomedical Named Entity Recognition with Multilingual BERT - Hakala Kai; Pyysalo Sampo (United States, 2025)
We present the approach of the Turku NLP group to the PharmaCoNER task on Spanish biomedical named entity recognition. We apply a CRF-based baseline approach and multilingual BERT to the task, achieving an F-score of 88% on the development data and 87% on the test set with BERT. Our approach reflects a straightforward application of a state-of-the-art multilingual model that is not specifically tailored to either the language nor the application domain. The source code is available at: https://github.com/chaanim/pharmaconer
Proceedings of The 5th Workshop on BioNLP Open Shared Tasks